A Study of Production Planning Based on the Linear Programming Method - Guo, Xiaowei (2020 9th International Conference on Industrial Technology and Management (ICITM), 2020)
This paper studies the production planning problem through the linear programming method. The study examines that it is an efficient method of operation research in the field of industrial engineering. Using the data of a Chinese company Z, which is a famous food company, the study analyzes the empirical results and obtains the following evidences. Firstly, the linear programming theory is very consistent with the actual production situation in China. Secondly, the real data of the company Z is used to derive the gross margin of one-unit product especially via the opportunity cost principle. Finally, one-period decision problem can be easily solved by the linear programming method and the results are reasonable and robust. In addition, the multi-period decision problem can be easily extended from one-period decision problem.